Conflict As A Trigger For The Development Of Self-Actualization In The Character Bambang In The Novel Sendiri By Tere Liye: A Humanistic Psychoanalytic Study - Permadi, Yudi; Laila, Anggun; Hazbini, Hazbini (International Journal of Research in Community Services, 2025)
This study aims to analyze conflict as a trigger for the development of self-actualization in Bambang's character in the novel Sendiri by Tere Liye using Abraham Maslow's humanistic theory which states that human needs are stratified. The research was conducted with qualitative descriptive method through data analysis that connects Maslow's five needs: physiological, security, love and existence, appreciation, and self-actualization. The results showed that Bambang's character successfully developed the fulfillment of basic needs through conflicts that occurred in the plot and achieved self-actualization in Maslow's hierarchy of needs.